2022
DOI: 10.1002/hed.27045
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery with neck dissection versus nonsurgical treatment in stage I and II human papillomavirus‐negative oropharyngeal cancer

Abstract: Background: Surgery + adjuvant therapy was shown to have improved overall survival (OS) versus nonsurgical treatment in T1-T2N1-N2b human papillomavirus (HPV)-negative oropharyngeal cancer (OPC). Our objective was to compare OS in transoral robotic surgery (TORS) with neck dissection versus nonsurgical treatment for T1-T2N0 HPV-negative OPC. Methods: Patients with T1-T2N0 HPV-negative OPC were identified in the National Cancer Database. OS was compared between groups: (1) TORS with neck dissection +/À adjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Therefore, it is necessary to use nebulizer therapy for patients suffering from viscous sputum and expectoration difficulty. Besides, margin status has been demonstrated to be an important prognostic factor, especially in HPV‐negative OPSCC, the positive rate of surgical margin was more easily obtained, up to 17.3% 36–38 . In our series, only three patients have carcinoma in situ in the postoperative pathological analysis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Therefore, it is necessary to use nebulizer therapy for patients suffering from viscous sputum and expectoration difficulty. Besides, margin status has been demonstrated to be an important prognostic factor, especially in HPV‐negative OPSCC, the positive rate of surgical margin was more easily obtained, up to 17.3% 36–38 . In our series, only three patients have carcinoma in situ in the postoperative pathological analysis.…”
Section: Discussionmentioning
confidence: 52%
“…Besides, margin status has been demonstrated to be an important prognostic factor, especially in HPV-negative OPSCC, the positive rate of surgical margin was more easily obtained, up to 17.3%. [36][37][38] In our series, only three patients have carcinoma in situ in the postoperative pathological analysis. Reports showed that HPVnegative OPSCCs located at the base of the tongue are more likely to have positive surgical margins in TORS.…”
Section: Follow-up and Survival Outcomesmentioning
confidence: 71%
“…Our results compared favourably with other studies demonstrating a low positive margin rate of 10.9%. There was a signi cant range in the variability of margin status in the literature ranging from 4-20%[13, 14,25]. In our study, patients with positive margins were more likely to have both locoregional and metastatic disease recurrence.…”
Section: Discussionmentioning
confidence: 54%
“…However, multiple modality therapy increases risk for treatment-related morbidity. Further, for early-stage HPV-negative oropharyngeal SCC, surgery may offer improved outcomes over chemoradiation, given reduced efficacy of non-surgical therapies ( 69 ). Similar concepts may be translatable to HPV-negative SCCUP and such trials investigating treatment options for HPV-negative are needed.…”
Section: Discussionmentioning
confidence: 99%